Regulation of Cancer Metastasis by TRAIL/Death Receptor Signaling - You-Take Oh (Biomolecules, 2021)
Death ligands such as tumor necrosis factor-related apoptosis-inducing ligand (TRAIL; TNFSF10) and their corresponding death receptors (e.g., DR5) not only initiate apoptosis through activation of the extrinsic apoptotic pathway but also exert non-apoptotic biological functions such as regulation of inflammation and cancer metastasis. The involvement of the TRAIL/death receptor signaling pathway in the regulation of cancer invasion and metastasis is complex as both positive and negative roles have been reported. The underlying molecular mechanisms are even more complicated. This review will focus on discussing current knowledge in our understanding of the involvement of TRAIL/death receptor-mediated signaling in the regulation of cancer cell invasion and metastasis.